Eosinophilic Esophagitis in a Developing Country: Is It Different from Developed Countries? - Abdulrahman Al-Hussaini; Toufic Semaan; Imad El Hag (Gastroenterology Research and Practice)
Background and Objective. Despite the extensive reporting of eosinophilic esophagitis (EoE) from industrialized developed countries, reports from developing countries are rare. The aim of our study was to determine the epidemiological, clinical, and endoscopic features of EoE and response to therapy in children and adults from a developing country, Saudi Arabia. Methods. We identified patients diagnosed with EoE in our center from 2004 to 2011. EoE was defined as esophageal mucosal infiltration with a peak eosinophil count ≥15 eosinophils/high-powered field. Results. Forty-five patients were diagnosed with EoE (37 children and 8 adults; 36 males; median age 10.5 years, range from 1–37 years). Feeding difficulty, vomiting/regurgitation, and failure to thrive predominated in young children, whereas dysphagia and food impactions predominated in older children and adults. Allergy testing revealed food sensitization in 12 of 15 patients (80%); 3 responded to elemental formula, while 8 failed to respond to dietary manipulation after the allergy testing. Thirty-nine patients achieved remission by swallowed inhaled fluticasone. The majority of patients experienced a recurrence of symptoms upon the discontinuation of fluticasone. Conclusion. Our data indicate that EoE is increasingly recognized in Saudi Arabia and show many similarities to data from North America and Europe.